Grounding line retreat of Totten Glacier, East Antarctica, 1996 to 2013 - Li, Xin; Rignot, Eric; Morlighem, Mathieu; Mouginot, Jeremie; Scheuchl, Bernd (Geophysical research letters, 2015)
Totten Glacier, East Antarctica, a glacier that holds a 3.9 m sea level change equivalent, has thinned and lost mass for decades. We map its grounding line positions in 1996 and 2013 using differential radar interferometry (InSAR) data and develop precise, high‐resolution topographies of its ice surface and ice draft using NASA Operation IceBridge data, InSAR data, and a mass conservation method. We detect a 1 to 3 km retreat of the grounding line in 17 years. The retreat is asymmetrical along a two‐lobe pattern, where ice is only grounded a few 10 m above sea level, or ice plain, which may unground further with only modest amounts of ice thinning. The pattern of retreat indicates ice thinning of 12 m in 17 years or 0.7±0.1 m/yr at the grounding line on average. Sustained thinning will cause further grounding line retreat but may not be conducive to a marine instability. Key Points Grounding line of Totten Glacier is retreating, not as fast as West Antarctica Retreat pattern explained by the newly inferred bed geometry If ice thinning maintains, bed geometry conducive to further retreat